Implementasi Kompetensi Kepribadian Guru Dalam Pembentukan Karakter Religius Santri Pondok Pesantren Nurulhuda Pekandangan Sumenep Jawa Timur Indonesia Tahun 2022 - Mohammad Shafli Al-Ayyubi; Mohammad Firdaus (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Teachers must be able to synchronize their behavior according to what they teach, meaning what the teacher says is in accordance with actions that can be seen from their daily behavior. The role of the teacher really determines the implementation of a good learning process in school. Where religious character is one of the character values ​​that is developed in school. However, there needs to be an in-depth study of what causes them to still have this non-religious attitude or is it outside of the religious attitude that has been instilled in them. The problem of this research is how effective the teacher's personality competence is in forming the religious character of the students of the Nurulhuda Islamic Boarding School, Pakandangan, Sumenep, and what can support and hinder the implementation of teacher personality competence in forming the religious character of the students of the Nurulhuda Islamic Boarding School, Pakandangan, Sumenep, the 2022-2022 school year. 2023. The approach used in this research is a qualitative approach with descriptive research type. There are three components to the data collection technique, namely observation, interviews and documentation. In this research, researchers used single case data analysis techniques (single case design) with the data analysis model introduced by Miles and Hiberman, namely the data analysis process was carried out simultaneously with data collection through several stages starting from the data collection process, presentation and verification or drawing conclusions . The research conclusion is that the effectiveness of teacher personality competence in forming the religious character of students at the Nurulhuda Islamic Boarding School in Pakandangan Sumenep for the 2022-2023 academic year is the involvement of teachers as motivators, mentors, educators, inspirers, evaluators and supervisors. Apart from that, the effectiveness of the teacher's personality competence is a role model for students, providing motivation and advice to students if they commit a violation and there is always time for students even outside class hours. Where these forms are gentle, disciplined, responsible and fair. Supporting factors for implementing teacher personality competence in forming the religious character of students at the Nurulhuda Pakandangan Islamic Boarding School, Sumenep for the 2022-2023 academic year are control and supervision as well as instructions from the boarding school leadership and cooperation and mutual assistance between teaching staff. Meanwhile, the inhibiting factors are inadequate infrastructure, insufficient financing, inadequate family support and supervision when students are at home.